(untitled) (Ius Novum, 2021)
Łukasz Kasprowicz’s article: The issue of privileges in the social security system (Part I and II) was published in issues No. 1/19 and 3/19 of the quarterly Ius Novum. The basic research problem of the article consists in the question whether the privileged retirement rights of selectedprofessional groups are justified in the light of the principles laid down in the Constitution of the Republic of Poland. The author states in the conclusions he is for the elimination of the majority of the privileges discussed and the development of a universal, uniform and coherent model of social security system covering all professional groups. Reading Ł. Kasprowicz’sarticle, one can get an impression that some of the issues discussed have not been exhaustively and comprehensively presented. The fragments concerning officers of uniform services as well as judges and prosecutors raise doubts. It seems that studying the regulations concerningprivileges in the social security system, Ł. Kasprowicz did not link them closely with the actual and legal conditions that have impact on the content of retirement rights of particular professional groups. In order to carry out an in-depth and objective assessment of the existing solutions and give a convincing answer to the question about grounds for differentiating the legal situation of beneficiaries of social rights, it is necessary to analyse many aspects of every single issue.